Impact of Financial Literacy on Financial Behavior among Sugarcane Farmers - Khadka, Yam Bahadur; Thapa, Bharat Singh (Nepalese Journal of Management and Technology, 2024)
This research investigates the status of financial literacy and its influence on the financial behavior of Sugarcane Farmers. Data were gathered between March and May of 2023 in Bardibas Municipality, Mahottari district, Nepal, involving 350 Sugarcane Farmers through face-to-face interviews utilizing a well-structured questionnaire. Analysis was conducted using Smart-PLS (version 4) and SPSS (version 22), calculating data frequency, percentage, mean, standard deviation, path coefficients, t-statistics, and R-squared. Hypotheses were tested employing path coefficients and t-statistics. The study reveals a significant, positive impact of financial literacy on financial behavior, encompassing saving, spending, investing, and borrowing behaviors. Notably, the research identifies a deficiency in financial literacy among these farmers, which correlates with diminished tendencies in saving, spending, and investing behaviors. Conversely, borrowing behavior remains relatively stable. These findings underscore the necessity for targeted financial literacy programs for sugarcane farmers in Nepal, emphasizing comprehension of financial concepts such as simple interest, compound interest, risk management, rational borrowing, and investment diversification. Such initiatives directly shape their financial decision-making and overall financial well-being, signaling important implications for policy-makers.